The Implementation of the Fun School Movement (GSM) in Moral Education at MI Soebono Mantofani, Tangerang - Azmi, Nurul; Syarif, Fajar (DAYAH: Journal of Islamic Education, 2025)
This study examines the implementation of the Fun School Movement (Gerakan Sekolah Menyenangkan/GSM) in moral education at MI Soebono Mantofani, South Tangerang. Using a qualitative case study design, data were collected through classroom and school-environment observations, semi-structured interviews with key stakeholders (school leaders, teachers, students, and parents), and document analysis. The findings indicate that GSM is implemented as a school-wide cultural orientation emphasizing emotional safety, student participation, and supportive learning routines. A central operational feature is the use of thematic classroom zones that function as routine reference points to structure interaction and reinforce moral habituation. The Emotional Zone supports attention to students’ readiness before learning, while Attendance and Aspiration Zones reinforce discipline routines and future orientation; the Goodness Zone provides moral reminders linked to everyday behavior. Teachers and parents perceived moral education as integrated into daily practice through habituation, teacher modeling, and value consistency across school and home contexts. The study suggests that GSM supports moral education by translating values into visible and repeated classroom routines, sustained through leadership commitment and parental involvement. Abstrak Penelitian ini mengkaji penerapan Gerakan Sekolah Menyenangkan (GSM) dalam pendidikan akhlak di MI Soebono Mantofani, Tangerang Selatan. Penelitian menggunakan desain studi kasus kualitatif. Data dikumpulkan melalui observasi kelas dan lingkungan sekolah, wawancara semi-terstruktur dengan pemangku kepentingan utama (pimpinan sekolah, guru, siswa, dan orang tua), serta analisis dokumen. Hasil penelitian menunjukkan bahwa GSM diterapkan sebagai orientasi budaya sekolah yang menekankan keamanan emosional, partisipasi peserta didik, dan rutinitas belajar yang suportif. Salah satu fitur operasional utama adalah penggunaan zona-zona tematik di kelas yang berfungsi sebagai rujukan rutinitas untuk menata interaksi dan memperkuat pembiasaan nilai. Zona Emosi mendukung perhatian terhadap kesiapan peserta didik sebelum pembelajaran, sedangkan Zona Kehadiran dan Zona Harapan memperkuat pembiasaan disiplin dan orientasi masa depan; Zona Kebaikan menjadi pengingat nilai yang dikaitkan dengan perilaku sehari-hari. Guru dan orang tua memandang pendidikan akhlak terintegrasi dalam praktik harian melalui pembiasaan, keteladanan guru, dan konsistensi nilai antara sekolah dan rumah. Penelitian ini menunjukkan bahwa GSM mendukung pendidikan akhlak melalui penerjemahan nilai ke dalam rutinitas kelas yang tampak dan berulang, dengan dukungan kepemimpinan sekolah dan keterlibatan orang tua.